1974
DOI: 10.1111/j.1365-2621.1974.tb17986.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Certain Muscle, Cartilage and Bone Traits to Tenderness of the Beef Longissimus

Abstract: S Histological and chemical characteristics of longissimus muscle and physical measurements of scapular and vertebral cartilage and bone were related to the tenderness of the beef longissimus. The 195 wholesale ribs were selected from carcasses differing widely in physiological maturity. Smaller diameter muscle fibers, longer sarcomeres, shorter muscle fiber fragments following homogenization, lower percentages of wavy fibers, decreased collagen content, increased percentages of soluble collagen, lower myofibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…(1974a) reported that correlation coefficients between individual carcass maturity indices (ossification in specific vertebral areas, color/shape of rib bones, color/texture of the lean) and specific palatability traits of cooked rib steaks were all of nearly the same magnitude. They concluded from their results (Berry et al 1974a) that physiological changes indicative of maturity apparently occur, in concert, at the same rate in all tissues evaluated, across a broad (A through E) range in physiological maturity; thus relationships between individual carcass maturity indicators and a palatability trait are quite similar. Multiple regression analyses were computed using the seven carcass maturity indices identified in Table 3.…”
Section: Resultsmentioning
confidence: 94%
“…(1974a) reported that correlation coefficients between individual carcass maturity indices (ossification in specific vertebral areas, color/shape of rib bones, color/texture of the lean) and specific palatability traits of cooked rib steaks were all of nearly the same magnitude. They concluded from their results (Berry et al 1974a) that physiological changes indicative of maturity apparently occur, in concert, at the same rate in all tissues evaluated, across a broad (A through E) range in physiological maturity; thus relationships between individual carcass maturity indicators and a palatability trait are quite similar. Multiple regression analyses were computed using the seven carcass maturity indices identified in Table 3.…”
Section: Resultsmentioning
confidence: 94%
“…1973). Decreased collagen content and increased collagen solubility are generally thought to positively impact beef tenderness (Berry et al . 1974; Light et al .…”
Section: Discussionmentioning
confidence: 99%
“…Of factors considered of primary importance in determining tenderness and overall palatability of cooked beef in the MSA grading system, there is ample US research-study support for use of marbling (Smith et al 1969(Smith et al , 2007Savell et al 1987Savell et al , 1989George et al 1999;Wyle 2000;Platter et al 2003bPlatter et al , 2005Gruber et al 2006), maturity (Berry et al 1974a(Berry et al , 1974bSmith et al 1982Smith et al , 1988Smith et al , 2008Hilton et al 1998), amount of B. indicus genetics (McKeith et al 1985a(McKeith et al , 1985bSherbeck et al 1995Sherbeck et al , 1996O'Connor et al 1997), sex (Choat et al 2006;Tatum et al 2007), tenderstretch carcass suspension (Smith et al , 1979(Smith et al , 2007Orts et al 1971;Hostetler et al 1975), ultimate pH (Smulders et al 1990;Tatum 1991a, 1994;Eilers et al 1996;Wulf et al 1997), meat colour (Jeremiah et al 1972;Wulf et al 1997;Cannell et al 2000;Wyle et al 2003;Vote et al 2003), fat colour (Hilton et al 1998;Wyle et al 1998Wyle et al , 2003Wyle 2000;Vote et al 2003) and subcu...…”
Section: Advantages Of the Tqm Approach To Assessing Beef Qualitymentioning
confidence: 99%